2015
DOI: 10.1080/00380768.2015.1078219
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Cd concentrations in different vegetables and those in arable soils, and food safety evaluation of vegetables in Taiwan

Abstract: The cadmium (Cd) accumulation capacity of various vegetables and the relationship between Cd concentrations in edible parts of vegetables and those in soils were assessed by conducting field experiments at Cdcontaminated sites in northern and central Taiwan. In addition, to thoroughly assess Cd concentrations in vegetables and to understand the food safety of vegetables in Taiwan, 2257 paired vegetable and surface soil samples were collected from major vegetable production areas for Cd concentration analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Air-dried soil samples were passed through a 2 mm sieve, homogenized, and stored in plastic vessels. The basic properties of the test soil, namely soil pH [ 50 ], organic matter [ 51 ], cation exchange capacity [ 52 ], the available Cd concentration [ 53 ] and the total Cd concentration [ 54 ], were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Air-dried soil samples were passed through a 2 mm sieve, homogenized, and stored in plastic vessels. The basic properties of the test soil, namely soil pH [ 50 ], organic matter [ 51 ], cation exchange capacity [ 52 ], the available Cd concentration [ 53 ] and the total Cd concentration [ 54 ], were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Leafy vegetables such as pakchoi, Chinese leek, water spinach, and lettuce have higher Cd accumulations in their edible parts compared to other vegetables belonging to the cucurbitaceae and solanaceous families. , In a study involving 18 plant species, Indian mustard and oilseed rape showed significantly higher Cd accumulation capacity in the same contaminated soil, with 10- and 66-fold higher accumulations compared to other species . Among 29 vegetable species, the top 5 Cd accumulators are peanut, amaranth, spinach, gynura, and okra, while the bottom 5 Cd accumulators are bitter gourd, cucumber, asparagus bean, snap bean, and sponge gourd . Similarly, another study reported the highest Cd accumulation in water spinach and the lowest accumulation in sweet pea among 28 vegetable species, with a maximum variation of 110-fold and 175-fold at two soil Cd levels (1 and 2 mg/kg) …”
Section: Feasibility Of the Cd-pscs Breedingmentioning
confidence: 99%
“…Cd was considered to be the most toxic (0.00-16.8 mg/kg), and Cu was found to contaminate the central area (4.43-217 mg/kg). In Taiwan, Lin et al [33] also reported soil contamination by Cd in Taoyuan (1.90-19.4 mg/kg) and Taichung (0.48-3.89 mg/kg). These results suggest that health risks should be taken into consideration for the food safety of local crops.…”
Section: Vegetable Growthmentioning
confidence: 99%